ANALISIS MINAT MASYARAKAT DALAM MENGAJUKAN PEMBIAYAAN DI PT. BPRS AMANAH UMMAH KANTOR CABANG CICURUG (Studi Pada Kecamatan Cicurug Kabupaten Sukabumu, Jawa Barat) - Mohammad Husen; Rully Trihantana; Miftakhul Anwar (SAHID BANKING JOURNAL, 2021)
ABSTRACT Bank is a financial intermediary institution that collects public funds from parties who have excess funds and distributes funds to those in need. Financing is an activity of Islamic banks in channeling funds to other parties based on sharia principles. Distribution of funds in the form of financing is based on the trust given by the owner of the funds to the user of the funds. Financing in Islamic banks uses contracts according to needs such as buying and selling there are murabahah, salam and istishna, in the form of cooperation there are mudharabah and musyarakah, in leasing services there are ijarah and IMBT as well as a deposit in the form of qordh. . Customer interest is a form of desire and interest in a decision-making process that will be carried out by consumers or customers. There are several stages in the decision-making process that are generally carried out by someone, namely the introduction of consumer needs and information processing. This study aims to examine how the influence of service, reputation and procedure variables influence or not the public's interest in proposing financing. The research method used in this study is research using quantitative methods. Quantitative research methods are used to examine certain populations or samples, with the aim of testing established hypotheses. The type of research used is descriptive quantitative with a field research approach. From the results of this study it can be concluded that partially the service and procedure variables have an effect on interest while the reputation variable has no effect. Simultaneously the service, reputation and procedure variables simultaneously influence the interest variable.